Multidisciplinary Treatment in Non-Syndromic Cleft Lip and Palate Patients: 2 Case Reports - Ozgür Inan; Gulsum Sayın Ozel; Dogan Dolanmaz; Ali İhya Karaman (Cumhuriyet University, 2018)
Objective: It is intended in this case report to explain the multidisciplinary treatment of 2 non-syndromic cleft lip and palate patients with different approaches, the treatment phases of prosthetic rehabilitation and the results obtained. Case Reports:15-year-old unilateral cleft lip and palate patient and 25-year-old bilateral cleft lip and palate patient was admitted to our clinic with the functional and aesthetic complaints. Orthodontic, surgical and prosthetic treatments were applied Results: With multidisciplinary treatments aesthetic and functional solutions were provided. Aesthetic and functional results were obtained for both cases with fixed restorations. The treatments protocols had no complications. The outcomes were of high quality and brought satisfaction to the patients. Conclusion: Multidisciplinary treatment should be considered in cleft lip and palate patients in order to be able to fully ensure speech and hearing, continuation of occlusion and maxillofacial growth in the normal course and the improvement of physical appearance and psychological state. However, different treatment plans should be considered in its different timing for each case.